1974
DOI: 10.1073/pnas.71.2.578
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Forms of DNA Polymerase in Mouse Myeloma

Abstract: Five distinct forms of DNA polymerase (deoxynucleosidetriphosphate: DNA deoxynucleotidyltransferase, EC 2.7.7.7) were separated from extracts of mouse myeloma MOPC-104E using a fractionation procedure based upon sequential iop-exchange column chromatography. The The existence of multiple forms of DNA polymerase in eukaryotic tissues is well established (1-9). The extent of the multiplicity and nature of the enzymes involved are matters of current investigation. DNA polymerases that exhibited apparently novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

1975
1975
1998
1998

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 19 publications
3
17
0
Order By: Relevance
“…(dT),, as primertemplate was observed. Since a poly(rA)-dependent DNA polymerase enzyme (synthetic RNA-dependent or R-DNA polymerase) found in a wide variety of eukariotic cell types [12,29,33,54-561 was also discovered in soluble extract of rat liver [53,57], the above observed activity may be the result of contamination with RNA-dependent DNA polymerase. This activity has been reported to be separable from DNA-dependent DNA polymerase [53,57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(dT),, as primertemplate was observed. Since a poly(rA)-dependent DNA polymerase enzyme (synthetic RNA-dependent or R-DNA polymerase) found in a wide variety of eukariotic cell types [12,29,33,54-561 was also discovered in soluble extract of rat liver [53,57], the above observed activity may be the result of contamination with RNA-dependent DNA polymerase. This activity has been reported to be separable from DNA-dependent DNA polymerase [53,57].…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation in the absence of one or more deoxynucleotides with other highly purified mammalian DNA polymerases has been reported [12,16,28].…”
Section: Properties O J Rat Liver Dna Polymerasesmentioning
confidence: 99%
“…Multiple forms of DNA polymerases have been detected in a number of eukaryotic organisms, and these enzymes have very different properties (Wallace et al 1971;Chang and Bollum 1971;Sedwick et al 1972;Matsukage et al 1974;Lynch et al 1975;Brakel and Blumenthal 1977;Weissbach 1977). Activity varies markedly depending on the developmental or physiological state of the cells (Chiu and Sung 1972;Benbow et al 1975;Ford et al 1975;Bertazzoni et al 1976;Spadari et al 1978).…”
Section: Introductionmentioning
confidence: 99%
“…All cells so far studied have shown more than one enzyme with DNA polymerase properties (Holmes & Johnston, 1975;. Further, it has been demonstrated that enzymic activities can be associated with subcellular structures such as nuclei (Bernard et al, 1974), mitochondria (Meyer & Simpson, 1970) and cytoplasmic membrane fractions (Matsukage et al, 1974). Moreover it has been established that in DNA-containing virions multiple activities of DNA-dependent DNA polymerase can be separated by ion-exchange chromatography (Lin et al, 1973).…”
mentioning
confidence: 99%